Amazônia usurpada e o direito ao passado regional: um estudo sobre a História Regional no Currículo da Secretaria Municipal de Educação de Manaus (1989 – 2020) - MENDONÇA, Marúcio José Bezerra (Universidade Federal do Pará, 2023)
The objective of the present research was to understand how the teaching of Regional History has been given in municipal public schools in the city of Manaus, presenting a methodological alternative based on the use of Didactic Sequence to streamline the teaching of Regional School History. In this sense, we seek to trace the advances and setbacks of Regional History in the curricular proposals of the Municipal Department of Education of Manaus (SEMED), starting from the analysis of the curricular proposals elaborated for the subject of Fundamentals of History of Amazonas - FHA, between the last decade of the 20th century and the first decade of the 21st century, when there was its extinction, and the curricular proposals for the teaching of History elaborated in the second decade of the 21st century. The arguments made in the different written and oral sources indicated that the Regional History presented in the curricular proposals of Manaus has been restricted to the teaching of the History of the State of Amazonas, with the idea of an Amazonian identity being forgotten in these debates. We analyze the conceptions and challenges presented by teachers about the teaching of Regional History and the struggle for the return of contents on Regional History to the curriculum. The locus was the Escola Municipal Helena Augusta Walcott, one of the educational units of SEMED-Manaus, located in the eastern zone of Manaus. The field research for the elaboration of the educational intervention proposal was carried out between two classes, one from the 7th grade and the other from the 8th grade, in the morning shift. Based on diagnoses, reality and students' school knowledge, we present a proposal for a Didactic Sequence called Usurped Amazon: the right to the regional past, conceived from the decolonial ideals, as a methodological strategy to dynamize and enhance the teaching of History.